2019
DOI: 10.1155/2019/5602904
|View full text |Cite
|
Sign up to set email alerts
|

Novel Protein-Repellent and Antibacterial Resins and Cements to Inhibit Lesions and Protect Teeth

Abstract: Orthodontic treatment is increasingly popular as people worldwide seek esthetics and better quality of life. In orthodontic treatment, complex appliances and retainers are placed in the patients’ mouths for at least one year, which often lead to biofilm plaque accumulation. This in turn increases the caries-inducing bacteria, decreases the pH of the retained plaque on an enamel surface, and causes white spot lesions (WSLs) in enamel. This article reviews the cutting-edge research on a new class of bioactive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
(132 reference statements)
1
6
0
Order By: Relevance
“…The marked reduction in BSA adsorption and the adsorption of proteins from the BHI medium with the increasing SB content observed in this study suggests SB-incorporated resin-based sealants can prevent the formation of such proteinaceous pellicles. Similar findings were reported in earlier studies that described the incorporation of other QAS such as dimethylaminohexadecyl methacrylate [15,23], methacryloyloxyethyl phosphorylcholine [10], and octafluoropentyl methacrylate [27]. The influence of sulfobetaine in particular has also been substantiated in earlier studies analyzing surface coatings [14,28,29], including dental varnish [10].…”
Section: Protein Adsorptionsupporting
confidence: 86%
See 1 more Smart Citation
“…The marked reduction in BSA adsorption and the adsorption of proteins from the BHI medium with the increasing SB content observed in this study suggests SB-incorporated resin-based sealants can prevent the formation of such proteinaceous pellicles. Similar findings were reported in earlier studies that described the incorporation of other QAS such as dimethylaminohexadecyl methacrylate [15,23], methacryloyloxyethyl phosphorylcholine [10], and octafluoropentyl methacrylate [27]. The influence of sulfobetaine in particular has also been substantiated in earlier studies analyzing surface coatings [14,28,29], including dental varnish [10].…”
Section: Protein Adsorptionsupporting
confidence: 86%
“…Moreover, dental cements and resin-based composites containing zwitterions, including methacryloyloxyethyl phosphorylcholine (MPC) and dimethylaminohexadecyl methacrylate (DMAHDM), have recently been reported. These studies have indicated that the modified resin moieties can impart an improved bacterial resistance [8,15,16]. However, the incorporation of SB into the resin base as a preventive therapy agent has rarely been reported [10].…”
Section: Introductionmentioning
confidence: 99%
“…Novel polymethyl methacrylate resins are known to repel bacterial adhesion, suppress oral biofilms and acid production. Chemically stable and nonvolatile polymeric antibacterial agents exhibit antimicrobial activity by influencing and interrupting bacterial cell membranes [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the field of dental materials, various attempts have been made to use MPC in protein-repellent dental composites, bonding agents, cements, and coatings to remove bacterial adhesion, reduce acid production, and protect tooth structure [25][26][27][28]. According to Zhang et al, MPC can reduce the adhesion of bacteria but does not have the ability to sterilise, that is, to directly kill bacteria.…”
Section: Introductionmentioning
confidence: 99%